Association between serum hepcidin level and restless legs syndrome. Issue 4 (8th February 2018) - Dauvilliers, Yves; Chenini, Sofiene; Vialaret, Jérôme; Delaby, Constance; Guiraud, Lily; Gabelle, Audrey; Lopez, Regis; Hirtz, Christophe; Jaussent, Isabelle; Lehmann, Sylvain
Abstract: Background: To better understand the role of iron homeostasis dysregulation in restless legs syndrome, we compared serum hepcidin and ferritin levels in drug‐free patients with primary restless legs syndrome and healthy controls and studied the relationship between hepcidin level and restless legs syndrome severity. Methods: One hundred and eight drug‐free patients with primary restless legs syndrome (65 women; median age, 61.5 years) and 45 controls (28 women; median age, 53.9 years) were enrolled. Inclusion criteria were: normal ferritin level (>50 ng/mL) and absence of iron disorders, chronic renal or liver failure, and inflammatory or neurological diseases. Each subject underwent a thorough clinical examination and a polysomnography assessment. Serum hepcidin‐25 was quantified using a validated mass spectrometry method. Restless legs syndrome severity was evaluated according to the International Restless Legs Syndrome Study Group. Results: Despite no group difference between normal ferritin levels and demographic features, serum hepcidin level and hepcidin/ferritin ratio were higher in patients than in controls. Hepcidin level and hepcidin/ferritin ratio, but not ferritin level, were positively correlated with periodic leg movements during sleep and wakefulness in the whole sample. Hepcidin level seem to be associated with restless legs syndrome severity in a complex U‐shaped relationship, without relationship with age at restless legs syndrome onset, positive family history, sleep and depressive symptoms, genetic background, and polysomnographic measurements. No relationship was found between ferritin level and restless legs syndrome severity. Conclusion: In drug‐free patients with primary restless legs syndrome, hepcidin level is higher than in controls and may be associated with restless legs syndrome clinical severity. This result emphasizes the complex peripheral iron metabolism deregulation in restless legs syndrome, opening potential perspectives for a personalized approach with a hepcidin antagonist. © 2018 International Parkinson and Movement Disorder Society